Boundedness of the gradient of a solution for the fourth order equation in general domains - Jia, Gao; Wei, Liu; Wei, Liu; Qi, Honghong; Qi, Honghong (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Based on new integral estimate, we establish boundedness of the gradient of a solution for a fourth order equation in an arbitrary three-dimensional domain.